THE ROLE OF THE NATIONAL LAND AGENCY IN ISSUING LAND RIGHTS CERTIFICATES (BPN DELI SERDANG STUDY) - Muhammad Miftahul Azhmi; Taufik Siregar; Wenggedes Frensh (SOSIOEDUKASI, 2026)
This research examines in depth the role of the National Land Agency (BPN) in issuing land title certificates, with a case study focus on the BPN Deli Serdang. Land title certificates are a fundamental instrument to ensure legal certainty and protection of land ownership rights for the community. This research outlines three main problems: (1) What are the legal regulations for issuing land title certificates based on statutory regulations? (2) What is the role of the BPN Deli Serdang in issuing land title certificates? (3) What are the obstacles faced by the BPN Deli Serdang in issuing land title certificates? This research uses a normative juridical legal research method with an analytical descriptive type. The normative juridical approach is applied to analyze related regulations. The data used include primary and secondary data, with qualitative descriptive data analysis. The results of the study show that (1) The legal rules for issuing land title certificates according to statutory regulations are Law No. 5 of 1960 concerning the Basic Agrarian Law, Government Regulation of the Republic of Indonesia Number 24 of 1997 concerning Land Registration, and Regulation of the Minister of ATR/BPN No. 1 of 2021 concerning Electronic Certificates. (2) The role of the Deli Serdang BPN in issuing land title certificates is to provide direction to applicants regarding the filing requirements needed to issue their land title certificates. (3) Obstacles faced by the Deli Serdang BPN in issuing land title certificates are the lack of human resources (HR) who have skills in the field of issuing land title certificates, so this becomes an obstacle for a Deli Serdang BPN agency in issuing land title certificates.